Simultaneous Cervical and Lumbar Spinal Degenerative Stenosis: Diagnostic andTreatment Challenge - Wendlassida Joelle Stéphanie (Indonesian Rheumatology Associantion, 2023)
Background: In simultaneous cervical and lumbar degenerative stenosis (tandem spinal stenosis), the cervical clinical signs may mask the lumbarones. Treatment is initially conservative in non-plegic cases. In the event ofsurgery, there is no consensus regarding the segment to be approached first.The purpose of this work was to describe our management of this condition. Methods: This was a 6-year retrospective study in the rheumatology andneurosurgery departments. All usable medical records of cases ofsimultaneous degenerative stenosis of the cervical and lumbar spine wereincluded. Results: We retained 84 squares. The average age was 57.1 years;the sex ratio 0.9. All the patients presented cervical and lumbar clinicalsigns. They had started at the lumbar spine in 46 cases (54.8%) and cervicalin 38 cases (45.2%). A full spinal MRI had been performed in 50%.Conservative treatment was effective in 36 patients (42.9%). Of the 32patients (66.7%) operated, 16 had been operated both the cervical andlumbar spine (7 simultaneous surgeries including percutaneous discolysisin one of the segments in 4 cases). The cervical spine had been operated onfirst in 7 of the 9 cases of staggered surgery. After an average follow-up ofone month, the evolution was favorable in 47 cases (56%); stationary 21(25%). Conclusion: Conservative treatment was effective in about half of thecases. Full spine MRI and staggered surgery were the most commonlyperformed. However, simultaneous surgery prioritizing the least aggressivegestures seems better.